2020
DOI: 10.1017/s1368980019003781
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality, nutrient intakes and biochemical status of New Zealand women of childbearing age according to alcohol consumption patterns

Abstract: Objective: To investigate associations between alcohol consumption patterns and diet quality, nutrient intakes and biochemical profile of women of childbearing age. Design: Nutrient intake data from 24 h diet recalls, alcohol consumption data and diet quality from the Dietary Habits Questionnaire, and biochemical analyses from the cross-sectional 2008/09 Adult Nutrition Survey in New Zealand. Setting: New Zealand households. Participants: New Zealand w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
1
0
1
Order By: Relevance
“…In the current study, we found significant differences in food consumption and nutrient intake between alcohol drinkers and non-drinkers, which were proportionally higher according to the number of beverages consumed per day. In general terms, diet quality worsened as alcohol consumption increased, in agreement with previous research [ 47 ]. Energy intake was higher in alcohol consumers.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we found significant differences in food consumption and nutrient intake between alcohol drinkers and non-drinkers, which were proportionally higher according to the number of beverages consumed per day. In general terms, diet quality worsened as alcohol consumption increased, in agreement with previous research [ 47 ]. Energy intake was higher in alcohol consumers.…”
Section: Discussionsupporting
confidence: 92%
“…Hazardous alcohol consumption is ranked above illicit drug use causing harm to our society, economics and health [ 9 ]. Excessive alcohol intake is frequently associated with unhealthy and risk-taking behaviours including poor dietary behaviours, false self-perceptions and psychological and anti-social disorders [ 39 , 40 , 41 ]. This study sheds light on gender, ethnicity, smoking, levels of PA or recreational sedentary screen-time as influential factors in the levels of alcohol consumption examined from information gathered from 1440 university students over nine years and covering three UK universities.…”
Section: Discussionmentioning
confidence: 99%
“…3 Carne vermelha: boi, porco, cabrito. 4 Consumo de doces como: sorvetes, chocolates, bolos, biscoitos e outros doces. Fonte: Francisco et al 8 .…”
Section: Variáveis Do Estudounclassified